Voluntourism : can universities make a difference that lasts a lifetime? - Abreu, Catarina Tavares de (2021)
The Voluntourism (VT) phenomenon combines volunteering with travelling. Despite the youth segment’s altruism within these social actions, critics question whether their contributions adequately address the local structural concerns. Students’ education as global citizens challenges universities through experiential learning opportunities that enrich the personal and professional self-development while acting towards the community development. However, the comprehension of the universities’ role among the remaining stakeholders in the international context is limited. Hence, the present dissertation intends to clarify how universities can redesign co-creation experiential learning programs to promote a win-win Voluntourism scenario. In this sense, this study explores the stakeholders’ perceptions of the universities’ intermediation in this touristic sector. Based on the conceptual analysis through Leximancer output, results underline the positive influence of these international experiences on universities to align with the students’ expectations and to include communities as part of their mission. These findings advance universities’ opportunity to focus beyond the knowledge transference while accounting for the education on social, cultural and emotional intelligence competencies. Also, when accounting for the interaction with international communities, universities mostly depend on VT operators. Still, this collaboration points out a way for Voluntourism regulation and accreditation by implementing monitoring and evaluation metrics. Thus, the practical and theoretical implications contribute to the literature finding a win-win path to Voluntourism, having universities as a crucial stakeholder.